The Integration of Islamic Values into the Environmental Education Curriculum in Urban Islamic Schools Based on the Adiwiyata Program Malang - Mukhlas Mukhlas; Muhamad Akip; Kunalan Kuriaya; Sujarwo Sujarwo; Miftahus Silmi Zohro (International Journal of Multidisciplinary Approach Research and Science, 2026)
The current environmental crisis not only reflects ecological degradation but also indicates a moral and spiritual decline, particularly in urban areas. Rapid urbanization has generated consumptive and exploitative lifestyles that erode ecological awareness, especially among students. In this context, Islamic education plays a crucial role in shaping environmentally responsible character grounded in faith-based values. This study aims to examine how Islamic values are integrated into environmental education in urban Islamic schools, with a specific focus on the implementation of the Adiwiyata program at MIN 1 Malang.This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with the principal and Adiwiyata program coordinators, observations of environmental activities, and analysis of relevant school documents.The findings reveal that Islamic values such as khalifah fil ardh (stewardship of the earth), amanah (trust), and rahmatan lil ‘alamin (mercy to all creation) have been effectively internalized through various initiatives, including the Sedekah Sampah (Waste Almsgiving) program, Green Friday activities, and thematic religious studies on environmental responsibility. These activities not only promote cleanliness and waste management practices but also cultivate students’ spiritual responsibility toward nature.The study concludes that the integration of Islamic values into environmental education strengthens students’ character formation and serves as an effective approach to addressing urban ecological challenges. Furthermore, this research offers a conceptual contribution to curriculum development and value-based educational practices in Islamic elementary schools.